Uso de tecnologia em maquetes interativas como recurso inclusivo - Ribeiro, Diego Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The oncern about accessibility and inclusion in education is growing today, largely due to the fact that we have laws that guarantee access for students with special needs in regular classrooms, highlighting the need to provide quality education and interaction with space for these students. satisfactorily. Because of this, the objective of this work is to study and elaborate an interactive didactic material, sound and tactile, adding the techniques of the Tactile Cartography with the cellular and the technology of the QR Code, that contributes positively to the teaching, being the student with special needs or not. Education is and always has been the greatest emancipation tool of the individual in society, especially in the case of students with a disability, so educators have an obligation to ensure an effective inclusion of these individuals in classrooms, providing adapted methodologies and materials that enable them. teach in such a way that they possess the theoretical, social and historical knowledge necessary to be active members in their communities. This work seeks not only to develop a material but also a teaching material and practice that contributes to the creation of inclusive pedagogical methodologies, which, when adapted to the student's reality, can guarantee a significant change for the teaching of students with disabilities. as a focus on visual impairment, but at the same time can be used with sighted students in a way that creates true inclusion

A preocupação com a acessibilidade e inclusão no ensino cresce atualmente, muito devido ao fato de termos lei que garantem o acesso de alunos com necessidades especiais em salas regulares, ressaltando a necessidade de proporcionar uma educação de qualidade e uma interação com o espaço para esses alunos de forma satisfatória. Devido a isso, o objetivo desse trabalho é o de estudar e elaborar um material didático interativo, sonoro e tátil, somando as técnicas da Cartografia Tátil com o celular e a tecnologia do QR Code, que contribua de forma positiva para o ensino, sendo o aluno portador de necessidades especiais ou não. A educação é e sempre foi a maior ferramenta de emancipação do indivíduo na sociedade, ainda mais no caso de alunos com alguma deficiência, então os educadores têm como obrigação garantir uma inclusão efetiva desses indivíduos em salas de aula, proporcionando metodologias e materiais adaptados que os ensinem de forma que eles possuam o conhecimento teórico, social e histórico necessário para serem membros ativos em suas comunidades. Este trabalho busca então não só desenvolver um material e sim uma material e uma prática de ensino que colabore para a criação de metodologias pedagógicas inclusivas, que ao serem adaptados à realidade do aluno, podendo garantir uma mudança significativa para o ensino de alunos com deficiência, como foco na deficiência visual, mas que ao mesmo tempo possa ser utilizado com alunos videntes de forma que crie uma verdadeira inclusão
Keywords: Cartografia; Educação inclusiva; Maquetes